Religion and youth educational aspirations: a multilevel approach - Nie, Fanhao (Journal of beliefs and values, 2019)
Previous research has demonstrated that individual religious beliefs and practices are associated with educational outcomes. However, less is known about the manner in which the overall religious cultural influence of a religion can affect an individual's educational aspirations. Using multilevel analyses on two waves of the National Study of Youth and Religion (NSYR) merged with county-level variables from the US Census, and the Religious Congregations and Membership Study (RCMS), the study shows that a county's higher Jewish population share is associated with a higher level of educational aspirations for the youth, regardless of being Jewish or not. This Jewish contextual effect remains robust even after controlling a wide range of individual and county-level variables, such as individual academic achievement and religious identity. Consistent with the relevant theory and literature, the negative main effect of county-level conservative Protestant population share on educational aspirations is explained by county-level socioeconomic characteristics. The same mechanism is used in part to explain the initially positive relationship between Catholic population share and educational aspirations. Finally, the study highlights the importance of using a multilevel approach to examine and provide understanding of the relationship between religious influence and educational outcomes.